Deskripsi Kejahatan Perampasan dan Pencurian Sepeda Motor Dengan Cara Kekerasaan (Begal) di Jalan Raya atau Lingkungan Masyarakat - Gunawan, Ade; Yusuf, Hudi (Media Hukum Indonesia (MHI), 2025)
In the last few days, the phenomenon of mugging crimes in certain areas. The latest case example is a police officer being mugged on the Kalimalang Inspection Road, Bekasi, Depok, and South Lampung. which was carried out sadistically using sharp weapons to firearms which has caused unrest in the community, mugging with violence often occurs in several areas in Indonesia. This crime not only causes material losses, but also someone's life, psychological for the victim and insecurity in society. This study takes the formulation of the problem of the factors causing mugging, its impact on victims and society, and steps that can be taken to prevent and overcome this crime. The results of the study show that the main factors driving mugging are difficult socio-economic conditions, such as poverty, unemployment, and social inequality. In addition, psychological factors such as the desire to show strength also play an important role. The impact of mugging is very large, both on victims who experience material losses and psychological trauma, as well as on the community who feel increasingly unsafe. To overcome this problem, synergistic efforts are needed between stricter law enforcement, increasing public awareness, and empowering local security groups. This study provides recommendations to strengthen socio-economic and security policies to effectively combat the phenomenon of mugging. The results of the study include: 1) What are the factors that influence the rampant motorcycle theft 2) How can the community maintain the security of their motorcycles 3) What is the role of the police in reducing cases of motorcycle theft 4) How does motorcycle theft impact on community life.